Critical digital literacy and cyber sexual harassment in higher education: a freirean perspective - Dian Paula April Juwan; Rr. Siti Murtiningsih; Sonjoruri Budiani Trisakti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Cyber sexual harassment (CSH) is becoming a bigger problem in digital academic settings, especially for college students who use online platforms a lot. While current responses frequently prioritize technical or regulatory solutions, there has been insufficient focus on pedagogical strategies that tackle the social and ethical aspects of digital violence. This study investigates the role of critical digital literacy, influenced by Paulo Freire’s humanist pedagogy, in fostering students’ critical awareness and ethical involvement concerning cyber sexual harassment. This study utilized a qualitative research design within a critical framework, involving 20 undergraduate students from three Indonesian universities. Data were gathered via semi-structured in-depth interviews and participatory observation during facilitated discussions regarding digital literacy and gender. Reflexive thematic analysis was used to look for patterns in how participants understood, experienced, and reacted to cyber sexual harassment in digital academic spaces. The results show that even though students are generally very aware of cyber sexual harassment, this awareness doesn't always lead to ethical behavior or a sense of collective responsibility. There were themes of normalcy, silence, and hesitation, as well as a lack of supportive or interventionist behaviors. Nevertheless, participants who participated in dialogical and reflective learning activities exhibited heightened awareness of digital power dynamics and the ethical ramifications of online behaviors. These results indicate that critical digital literacy can serve as an emancipatory educational approach that connects awareness with action. By encouraging conversation, thought, and critical awareness, colleges and universities can help fight cyber sexual harassment as a cultural and structural issue instead of just a problem with one person's behavior.